Intrapericardial instillation of recombinant tissue plasminogen activator: A case report - Rahman, A; Ilkay, E; Burma, O; Uyar, IS; Akkus, MN; Ozdemir, F; Cekirdekci, A (Futura Publ Co, 1998)
On the 43rd day after open heart surgery, pericardial effusion developed in a patient and resulted in cardiac tamponade. Since the drainage could not be obtained by subxiphoid window technique due to location of fluid and presence of fibrinous adherence and a thrombus in pericardial space, transcatheter intrapericardial recombinant tissue plasminogen activator (tPA) was instilled in the patient. Thus, the intrapericardial fibrinous adherence and the thrombus disappeared, and the effusion was drained efficiently.
Keywords: Open-Heart Surgery; Cardiac-Tamponade; Pericardial-Effusions; Streptokinase